Direction of the relationship between methamphetamine use and positive psychotic symptoms in regular methamphetamine users: evidence from a prospective cohort study. (July 2021) - Hides, Leanne; Chan, Gary; Dawe, Sharon; McKetin, Rebecca; Kavanagh, David J.; Young, Ross McD; Teesson, Maree; Saunders, John B.
Abstract : Background: Methamphetamine has been consistently associated with positive psychotic symptoms, but little is known about whether the reverse also occurs. Aims: This study determined whether the relationship between methamphetamine use and positive psychotic symptoms is bidirectional over 12 months. The impact of lifetime psychotic disorders and methamphetamine dependence on these relationships was also examined. Method: A total of 201 regular (at least monthly) primary methamphetamine users were recruited from free needle and syringe programmes in three Australian cities. Data on the frequency of methamphetamine and other drug use (from Timeline Followback inteviews) and the severity of positive psychotic symptoms (using the Brief Psychiatric Rating Scale) in the past 2 weeks were collected in 12 contiguous monthly face-to-face interviews (mean of 9.14/11 (s.d. = 3.16) follow-ups completed). Diagnoses were derived using the Psychiatric Research Interview for DSM-IV Substance and Mental Disorders. Results: The mean age of participants was 31.71 years (s.d. = 8.19) and 39% ( n = 77) were women. At baseline 55% ( n = 110) were dependent on methamphetamine and 51% ( n = 102) had a lifetime psychotic disorder. Cross-lagged dynamic panel models found a significant bidirectional relationship between psychotic symptoms and methamphetamine use (Comparative Fit Index (CFI) = 0.94, standardised root mean square residual (SRMR) = 0.05, root mean square error of approximation (RMSEA) = 0.05, 95% CI 0.04–0.06). The magnitude of the relationship in each direction was similar, and the presence of methamphetamine dependence or a lifetime psychotic disorder did not have an impact on results. Conclusions: A dynamic, bidirectional relationship between methamphetamine and psychotic symptoms of similar magnitude in each direction was found over 1 year. This suggests integrated treatments that target methamphetamine, psychotic symptoms and their interrelationship may be of most benefit.